Regulation of Hox gene activity by transcriptional elongation in Drosophila. - Chopra, V.S.; Hong, J.W.; Levine, M. (Current Biology, 2009)
Hox genes control the anterior-posterior patterning of most metazoan embryos. Their sequential expression is initially established by the segmentation gene cascade in the early Drosophila embryo [1]. The maintenance of these patterns depends on the Polycomb group (PcG) and trithorax group (trxG) complexes during the remainder of the life cycle [2]. We provide both genetic and molecular evidence that the Hox genes are subject to an additional tier of regulation, i.e., at the level of transcription elongation. Both Ultrabithorax (Ubx) and Abdominal-B (Abd-B) genes contain stalled or paused RNA polymerase II (Pol II) even when silent [3, 4]. The Pol II elongation factors Elongin-A and Cdk9 are essential for optimal Ubx and Abd-B expression. Mitotic recombination assays suggest that these elongation factors are also important for the regulation of Notch-, EGF-, and Dpp-signaling genes. Stalled Pol II persists in tissues where Ubx and Abd-B are silenced by the PcG complex. We propose that stalling fosters both the rapid induction and precise silencing of Hox gene expression during development.